Optimizing wastewater heat recovery systems in textile dyeing processes using pinch analysis. (September 2022) - Kim, Yurim; Lim, Jonghun; Shim, Jae Yun; Lee, Heedong; Cho, Hyungtae; Kim, Junghwan
Graphical abstract: Highlights: An optimal WWHR system for textile dyeing was developed using a two-step approach. The two-step approach comprises the scenario definition and pinch analysis. The cost-optimal WWHR system lowered the energy usage by 28.64% and TAC by 73.65%. The PBP of the optimal WWHR system was 4.32 y. Abstract: Textile manufacturing discharges large amounts of wastewater containing significant amounts of thermal energy. The textile dyeing process consists of several complex processes with different operating times, temperatures, and water usage. The absence of a suitable wastewater heat recovery (WWHR) system requires a large amount of energy for heating fresh water and cooling wastewater. Therefore, recovering wastewater while satisfying the operating conditions of each process is crucial. Herein, we suggest an optimal design for WWHR systems to maximize the energy efficiency in the textile dyeing process using pinch analysis by a novel two-step approach. First, the scenarios for all feasible WWHR methods were defined, and the WWHR systems were designed accordingly by integrating a heat pump and heat exchanger. Second, the heat exchanger network of the developed WWHR systems was modified based on pinch analysis to maximize the waste-heat recovery efficiency. Finally, to derive the cost-optimal WWHR system, a techno-economic analysis was conducted. The total annualized cost (TAC), based on the capital and operating cost, was determined based on current and potential future economies. The proposed energy-saving measures reduced the TAC by 28.6% and obtained a payback period of up to 4.3 y.